Applying the Investment Multiplier to Identify Key Points of Economic Growth - Mikhail Evgenievich Kosov; Vladimir Vladimirovich Eremin; Sergey Alekseevich Pobyvaev; Tural Sokhbat Ogly Gaibov (Ital Publication, 2022)
The crisis phenomena irregularity due to the COVID-19 pandemic requires new, to a certain extent, non-routine tools for their settlement, namely the action effect enhancers of the state and private investors to develop the economy in conditions of shrinking volumes of available financial resources. The paper proposes the Investment Multiplier (IM) as such a tool. The author's model was generated based on a detailed description of developing multiplier processes to analyze its action. The study aims to estimate the IM values of the economies of Kurgan, Sverdlovsk, and Chelyabinsk, the most industrially developed Russian regions, and identify the main points of their economic growth. The key research method was regression analysis. The present study establishes interconnectivity between marginal propensity and savings, marginal propensity and imports, marginal tax rate, and investment accelerator, and their influence on the regional multiplier. From a position of investment multiplier, the authors try to narrow the research gap in how investment policies influence the economic growth of the Russian regions. The study results determine IM values for the analyzed regions, identifying their differences and reasons. The key points of economic growth in these regions were identified. The scientific novelty involves applying changes in regional multiplier processes' dynamics to determine the key development points. The practical significance is that the IM value is an analytical tool that will identify existing key points of regional economic development and, by managing the IM value, create new points for investments with a large-scale multiplier effect, thus developing the regional economy. Doi: 10.28991/ESJ-2022-06-02-05 Full Text: PDF